The Influence of Company Size and Profitability on Company Value - Fitriya Muslimah Zam-Zam; Haliah; Andi Kusumawati (East Asian Journal of Multidisciplinary Research, 2023)
This study aims to determine the influence of company size and profits on company value through the dividend policy of manufacturing companies. The sample population of this study includes companies in the infrastructure sector listed on the Indonesia Stock Exchange (BEI) during the period 2019-2021. The sampling technique used in this study was purposive sampling, thus an initial sample of 61 companies was obtained for 40 companies. The data source in this study is secondary data. The data analysis techniques used were multiple linear regression and descriptive statistical analysis. Subject of this study shows that the sig value is 0.032 > 0.05 and the t number is 2.770 > t Table 2.262 on the impact of company size on company value, meaning that company size has an impact simultaneously positively affects company value, according to the impact of business size on business value. Subject II shows that the sig value is 0.032 > 0.05 and the t number is 1.571 < Table 2.262 means that there is no effect of profits on firm value. The test results show that business size has a significant positive impact on business value, while profitability does not have a positive impact on business value. The test results show that business size has a significant positive impact on business value, while profitability does not have a positive impact on business value.